ADP‐ribosylation of DNA moving into focus. (4th December 2017) - Dölle, Christian; Ziegler, Mathias
Abstract : In this issue of The FEBS Journal, Munnur and Ahel describe the reversible mono‐ADP‐ribosylation of DNA by PARP3, a member of the poly‐ADP‐ribose‐polymerase family known to modify proteins. They demonstrate a selective ADP‐ribosylation of the 5′‐phosphate group on DNA ends and show that the modification can be reversed by several known ADP‐ribosylhydrolases including PARG.